A Case Report: An Elderly Male Patient With Takayasu Arteritis After Coronary Artery Bypass Grafting - Yu, Huaitao; Liu, Wenzhao; Zhang, Yuan; Yan, Xuefang; Li, Na; Ti, Yun; Bu, Peili (Frontiers in Cardiovascular Medicine, 2021)
Background: Takayasu arteritis is a rare chronic granulomatous inflammation involving the aorta and its main branches. In this report, we describe an extremely rare elderly male patient with Takayasu arteritis after coronary artery bypass grafting. Case Summary: A 61 years old male patient with persistent precordial pain underwent angiography. Vascular murmurs could be heard in carotid artery and bilateral renal artery by auscultation. Laboratory parameters showed high Erythrocyte Sedimentation Rate and C-reactive protein. CT coronary angiography showed multiple stenosis of aorta and its main branches, such as carotid and renal artery involvement. Coronary angiography showed that the coronary artery had multiple branches stenosis, the left anterior descending artery had severe stenosis, the distal end of which was reversed to the right coronary artery , and the RCA was completely occluded. Because of the high level of markers of inflammatory activity, the patient began to take glucocorticoid. Although the patient still had multi branch stenosis of coronary artery, considering the patient's previous CABG operation history, surgery and interventional therapy were not feasible, the patient was given conservative drug for further treatment. After treatment, the inflammatory index was significantly descended, and N terminal-pro Brain natriuretic peptide was decreased. Discussion: A rare case of an elderly male patient with Takayasu arteritis after coronary artery bypass grafting was reported. In addition to hypertension, hyperlipidemia and other risk factors, coronary artery involvement caused by TA may be a major cause of aggravation of symptoms in patients with acute myocardial infarction, especially after CABG.